Percentage Area of Intimal Surface of the Infra-Renal Segment of Abdominal Aorta Affected by Atherosclerosis - A Postmortem Study (Bangladesh Journal of Anatomy, 2009)
Context: Atherosclerosis and its complications are still the major source of morbidity and mortality in the industrial world, and estimates have been offered that at its present rate of growth, will be the major cause of death from this disease by the year 2020 in the entire world, (Joseph 2004).The seemingly increased incidence of atherosclerotic disorders in the country, their fatal consequences and the paucity of relevant data, the present study was carried out to assess the percentage of area involved in atherosclerotic lesion of abdominal aorta of Bangladeshi males. Study design: Descriptive cross-sectional. Place & time of study: In the department of Anatomy, Sir Salimullah Medical College, Dhaka, during the study period of July 2005 to June 2006. Method: Abdominal aorta were collected from fifty Bangladeshi male dead bodies who underwent routine postmortem examination due to accidental death. Sudy was done to find out the macroscopic extent of atherosclerotic lesion of abdominal aorta (below the origin of renal arteries) from Bangladeshi male of different ages. The subjects were divided into lower (8-29), middle (30-40), higher (42-92) age groups. The atherosclerotic lesions were stained red by treating the aorta with sudden IV. The percentage of area on the intimal surface showing atherosclerotic lesion were measured by AutoCAD. Result: The percentage of area involved in atherosclerotic lesion was increase with advancing age. Unpaired student ‘t' test for statistical analysis revealed significant difference. (P